Retrospective analysis of breast cancer prognosis among young and older women in a Brazilian cohort of 738 patients, 1985–2002 - De Lima Vazquez, Fabiana (Oncol Lett, 2016)
Invasive breast cancer (BC) is infrequent among women aged ≤40 years, however, the disease outlook in these younger patients is generally worse than among older women. The present study aimed to compare socio-demographic, clinical and pathological characteristics, and their association with long-term survival, between two random cohorts of young (≤40 years) and older (50–69 years) Brazilian patients with BC. The cohort comprised of 738 randomly selected women who were diagnosed with BC at Barretos Cancer Hospital, Pio XII Foundation (Barretos, Brazil) between January 1985 and December 2002; the patients included young women (n=376) and older women (n=362). The current analysis suggested that BC in young women is associated with numerous pathological features of aggressiveness. Second cancer and bilateral BC were independent predictors of a poor outcome in the younger group. Furthermore, C-erB-2 was positively correlated with poor outcome in the older group, whereas estrogen receptor status and TNM stage were associated with disease prognosis in both groups. The overall survival rates of the two age groups were similar except when analyzed according the treatment period (1997–2002). Although patients aged ≤40 years harbored tumors with more aggressive clinicopathological characteristics, these characteristics were not independent predictors of overall survival. The present study indicates that medical advances associated with prevention of breast cancer may improve screening programs, which may therefore increase early diagnosis and subsequently lower mortality rates.